PENGARUH PENEMPATAN LOKASI PERUSAHAAN TERHADAP PENINGKATAN VOLUME PENJUALAN MOBIL HONDA PADA PT HONDA BONE INDAH - Sunarni, Sunarni; Syam, Marniati; Mursakin, Mursakin (LPPM Universitas Muhammadiyah Mamuju, 2024)
The purpose of this research is to determine the magnitude of the influence of company location on increasing Honda car sales Volume at PT Honda Bone Indah This research uses a census type of research wit a quantitative approach, which aims to test the influence of the indefendent variable on the devenden variable. The population in the study was only 15 employees and coustemer, and less than 30 people, so in this study all members of the population were determined to be respondents (total sampel/saturate sample). The data analysis method used in this research is simple regression analysis. The results of this research show that 1) the placemen of sales locations has a positive effect on increasing the sales Volume of Honda Bone Indah, Bpne Regrency, this Is reflected in the sales location placemen variable wit an average score of 82.40% in the good category 2) meanwhile, the variable for increasing Honda Car sales Volume with an average score of 79.55 % in the good category.